2017
DOI: 10.1097/bsd.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Paraspinal Muscle Cross-sectional Area After Lumbar Decompression

Abstract: Compared with the open approach for lumbar stenosis, MEDS had significantly less negative impact on the paraspinal muscle CSA. Previous reports have documented negative effects of paraspinal muscle injury, including weakness, disability, and pain. Collectively, these data suggest that the MEDS approach for lumbar decompression is less destructive to the paraspinous muscles than the open approach and may facilitate better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 40 publications
0
46
1
Order By: Relevance
“…As described above, our methods of either reattaching the LM to the spinous process or attaching the ends of bilateral LM tendons to each other following laminectomy find their rationale in the successes of minimally invasive surgeries of the lumbar spine. Numerous studies have shown that minimally invasive surgeries, by avoiding the detachment of muscle tendons, decreasing muscle retraction and minimizing the size of the surgical corridor, maintain the integrity of the paraspinal musculature, are less damaging to the LM, and are associated with reduced incidences of postoperative LBP [1,9,13,19]. In a study by Fan et al, patients undergoing minimally invasive procedures of the lumbar spine had less postoperative back pain, LM atrophy, fatty infiltration, and functional disability as compared with patients undergoing conventional open posterior approach [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, our methods of either reattaching the LM to the spinous process or attaching the ends of bilateral LM tendons to each other following laminectomy find their rationale in the successes of minimally invasive surgeries of the lumbar spine. Numerous studies have shown that minimally invasive surgeries, by avoiding the detachment of muscle tendons, decreasing muscle retraction and minimizing the size of the surgical corridor, maintain the integrity of the paraspinal musculature, are less damaging to the LM, and are associated with reduced incidences of postoperative LBP [1,9,13,19]. In a study by Fan et al, patients undergoing minimally invasive procedures of the lumbar spine had less postoperative back pain, LM atrophy, fatty infiltration, and functional disability as compared with patients undergoing conventional open posterior approach [1].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the posterior approach on the integrity of the paraspinal musculature, particularly the LM, is concerning as studies have linked paraspinal muscle integrity to low back pain (LBP). Numerous reports have shown that patients with postoperative LBP exhibit gross and histological signs of LM degeneration, such as muscle atrophy (decreased crosssectional area [CSA]), LM intramuscular adipose tissue accumulation, and LM denervation [1,2,4,6,[8][9][10][13][14][15]. These findings have been attributed, in part, to the imprecise nature of the LM dissection as well as the intraoperative use of self-retaining retractors, both of which have been shown to result in ischemic necrosis, scar tissue formation, denervation, and atrophy [5,8,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bresnahan et al demonstrated a significant increase in the paraspinal muscle cross sectional area on MRI in patients who underwent an MIS decompression. 17 Although the imaging analysis was blinded, the results of postoperative paraspinal muscle hypertrophy were counterintuitive. The authors demonstrated significantly lower multifidus muscle atrophy in the MIS cohort as compared to the open cohort.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In addition, theses results are favorable when compared to data regarding paraspinal anatomy after traditional open posterior approaches. 11,19 Despite small heterogeneous patient populations 18,20 and some counterintuitive results 17 There are clear limitations to the current study. First, the sample size was relatively small, which may have contributed to the lack of statistical significance when comparing pre-and postoperative T1 signal intensity ratios.…”
mentioning
confidence: 96%
See 1 more Smart Citation